Improving New Vocabulary Learning in Context - Colombia Ovalle María (Universidad Nacional de Colombia, 2001)
The main purpose of this study is to help students increase their vocabulary learning in context because when learners participate in a special class with different activities and keep in mind the situation, they remember new words. The study was carried out in the action research method, and the activities provided to students encouraged learning and motivated them to practice English more.